β‐Ketoenamine‐Linked Covalent Organic Frameworks Synthesized via Gel‐to‐Gel Monomer Exchange Reaction: From Aerogel Monoliths to Electrodes for Supercapacitors - Martín‐Illán, Jesús Á.; Sierra, Laura; Guillem‐Navajas, Ana; Suárez, José Antonio; Royuela, Sergio; Rodríguez‐San‐Miguel, David; Maspoch, Daniel; Ocón, Pilar; Zamora, Félix (Advanced functional materials, 2024)
Covalent organic frameworks (COFs) possess intrinsic nanoscale pores, limiting mass transport and impacting their utility in many applications, such as catalysis, supercapacitors, and gas storage, demanding efficient diffusion throughout the material. Hierarchical porous structures, integrating larger macropores with inherent micro‐/meso‐pores, facilitate rapid mass transport. Recently, the fabrication of aerogel monoliths is reported exclusively from imine‐linked COFs, offering flexibility in aerogel composition. However, challenges in synthesizing robust β‐ketoenamine‐based COFs with comparable surface areas prompted innovative synthetic approaches. Leveraging the dynamic nature of COF bonds, in this work efficient monomer exchange from imine to partially β‐ketoenamine‐linked COFs within the gel phase is demonstrated. These aerogels can be transformed into electrodes using the compression technique. The new flexible electrodes‐based β‐ketoenamine‐linked COF composites with C super P exhibit superior durability and redox activity. Through supercapacitor assembly, the β‐ketoenamine‐linked COF electrodes outperform their imine‐based counterparts, showcasing enhanced capacitance (88 mF cm−2) and stability at high current densities (2.0 mA cm−2). These findings underscore the promise of β‐ketoenamine‐linked COFs for pseudocapacitor energy storage applications. The feasibility of monomer exchange to obtain β‐ketoenamine‐linked covalent organic frameworks (COFs) is shown in a monolithic gel‐to‐gel process. This allows the preparation of more robust COF aerogels and their easy processing into supercapacitor electrodes with superior performance compared to imine‐linked COFs, opening new opportunities in energy‐related applications.